2009
DOI: 10.1109/tcad.2009.2028681
|View full text |Cite
|
Sign up to set email alerts
|

ReSPIR: A Response Surface-Based Pareto Iterative Refinement for Application-Specific Design Space Exploration

Abstract: Abstract-Application-specific multiprocessor systems-on-chip (MPSoCs) are usually designed by using a platform-based approach, where a wide range of customizable parameters can be tuned to find the best tradeoff in terms of the selected figures of merit (such as energy, delay, and area). This optimization phase is called design space exploration (DSE), and it usually consists of a multiobjective optimization problem with multiple constraints. So far, several heuristic techniques have been proposed to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 35 publications
(54 reference statements)
0
91
0
4
Order By: Relevance
“…The distance between the Pareto sets have been compared using the Average Distance from Reference Set (ADRS) [17]. The ADRS is usually measured in terms of percentage and should be minimized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the Pareto sets have been compared using the Average Distance from Reference Set (ADRS) [17]. The ADRS is usually measured in terms of percentage and should be minimized.…”
Section: Resultsmentioning
confidence: 99%
“…For each state in s, all possible actions are applied, generating the configurations that differ from s0 by one parameter (lines [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. For all the generated configurations (obtained by applying a in si), s k metrics are partitioned, D and T P (si, a, s k ) are updated.…”
Section: Markov Decision Processmentioning
confidence: 99%
“…To adhere to the application hardware requirements, much prior research focused on configurable hardware (e.g., [13][14][15][16][17][18][19][20][21][22][23]), configurable caches (e.g., [3,4,[24][25][26][27]), and design space exploration (e.g., [5][6][7][9][10][11][28][29][30][31][32]). Given this expansive prior work, we discuss fundamentals of configurable hardware, followed by specific related work in configurable caches and design space exploration with fundamentals that are directly applicable to our approach.…”
Section: Related Workmentioning
confidence: 99%
“…The results revealed that a subset of size 4 (out of 18) configurations provided energy savings within 1% and 5% of the complete design space for the instruction and data cache, respectively. Palermo et al [29] developed a methodology that iteratively eliminated the evaluated configurations from the design space. On each iteration, a set of Pareto configurations was selected.…”
Section: Design Space Explorationmentioning
confidence: 99%
“…The third category is based on estimating metrics of interest under given configurations, as opposed to actually running time-consuming simulation or synthesis. Example estimators include Fuzzy Systems [2], Markov Decision Process [4], and response surface modeling [17]. These approaches cannot work alone and should be incorporated with optimization frameworks.…”
Section: Related Workmentioning
confidence: 99%